Comparison of the Mechanical Properties of Early Leukocyte- and Platelet-Rich Fibrin versus PRGF/Endoret Membranes - Hooman Khorshidi; Saeed Raoofi; Rafat Bagheri; Hodasadat Banihashemi (International Journal of Dentistry)
Objectives. The mechanical properties of membranes are important factors in the success of treatment and clinical handling. The goal of this study was to compare the mechanical properties of early leukocyte- and platelet-rich fibrin (L-PRF) versus PRGF/Endoret membrane. Materials and Methods. In this experimental study, membranes were obtained from 10 healthy male volunteers. After obtaining 20 cc venous blood from each volunteer, 10 cc was used to prepare early L-PRF (group 1) and the rest was used to get a membrane by PRGF-Endoret system (group 2). Tensile loads were applied to specimens using universal testing machine. Tensile strength, stiffness, and toughness of the two groups of membranes were calculated and compared by paired t-test. Results. The mean tensile strength and toughness were higher in group 1 with a significant difference (P<0.05). The mean stiffness in group 1 was also higher but not statistically significant (P>0.05). Conclusions. The results showed that early L-PRF membranes had stronger mechanical properties than membranes produced by PRGF-Endoret system. Early L-PRF membranes might have easier clinical handling and could be a more proper scaffold in periodontal regenerative procedures. The real results of the current L-PRF should be in fact much higher than what is reported here.